Fast-Switching SVR Weight Coefficient Design for the MPTC of Double Three-Phase PMSM - Huanzhen Zhang; Shaosheng Fan; Gongping Wu (Energies)
The dual three-phase permanent magnet synchronous motor (DT-PMSM) has the advantages of high fault tolerance, flexible control, small torque ripple, and meeting the requirements of low voltage and high power. However, in the traditional model of predictive torque control (MPTC) of DT-PMSM, the calculation is cumbersome due to the numerous voltage vectors. Therefore, a fast-switching table based on torque prediction DT-PMSM control is established. In addition, in the DT-PMSM conventional MPTC strategy, the cost function consists of the electromagnetic torque error and the stator flux error. Due to the lack of an explicit theory to guide the design of the weight coefficients, the weight coefficients can only be set through a large number of simulations and experiments in applications, and the tuning process is very cumbersome. Therefore, the support vector machine regression (SVR) method was used to improve the tedious calculation and tuning process of MPTC of DT-PMSM. The experimental results show that MPTC based on a fast-switching table achieves good steady-state and dynamic control performance by using weighting factors.